2005
DOI: 10.1117/12.623547
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized antireflective nanostructures on PMMA by ion etching

Abstract: Stochastic, self-organized nanostructures are produced by a low-pressure plasma treatment on the polymer polymethylmetacrylate (PMMA). The phenomena obtained by plasma treatment (structure formation and antireflective effect) are investigated regarding surface modifications, structure growth, and chemical modifications. Optically, the structure acts like a gradient layer with decreasing effective refractive index towards air, which is suitable for antireflection of PMMA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…These results, that the Ce 4+ was dominant in Ce oxide nanoparticles synthesized through the hydrothermal method in alkaline conditions, were already reported (Figure D). The above results revealed that CNPs were successfully fabricated with typical characteristics of ceria with catalytic effects due to their nanosize. Many researchers have combined CNPs with other biomaterials to overcome the inherent lack of certain properties, such as lower bioactivity and poorer mechanical properties. , PMMA, a widely utilized biomaterial, has been previously modified by CNPs to confer extra physicomechanical properties, but the antimicrobial effects have not yet been investigated in detail. Here, CNPs were incorporated into PMMA to overcome the inherent drawback of PMMA, its poor antimicrobial properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results, that the Ce 4+ was dominant in Ce oxide nanoparticles synthesized through the hydrothermal method in alkaline conditions, were already reported (Figure D). The above results revealed that CNPs were successfully fabricated with typical characteristics of ceria with catalytic effects due to their nanosize. Many researchers have combined CNPs with other biomaterials to overcome the inherent lack of certain properties, such as lower bioactivity and poorer mechanical properties. , PMMA, a widely utilized biomaterial, has been previously modified by CNPs to confer extra physicomechanical properties, but the antimicrobial effects have not yet been investigated in detail. Here, CNPs were incorporated into PMMA to overcome the inherent drawback of PMMA, its poor antimicrobial properties.…”
Section: Resultsmentioning
confidence: 99%
“…A meaningful augmentation of flexural strength in a 0.5% incorporated specimen was considered due to the optimal mix of CNPs and PMMA to resist outer force. In other literature, the flexural strength was also enhanced when inorganic nanoparticles such as mesoporous silica nanoparticles were doped in PMMA. Theoretically, the incorporation of nanoparticles into the polymer with physical binding is known to reinforce mechanical properties by generating bridging and crack deflection in the matrices. , Here, CNPs were considered to play a role as a crack deflector in the 0.5% specimen, while other conditions were suboptimal in terms of their lower amounts of reinforcement in the matrix or improper networking in the matrix . On the other hand, surface hardness, measured as the Vickers hardness, showed decreased values after the incorporation of CNPs into PMMA (Figure E, n = 10, P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…For PET, the following mechanisms have been postulated: (i) differential etching of crystalline and amorphous domains, (ii) dewetting of a polar fluid film of oxidized low molecular weight fragments in small drops that act as etch masks, and (iii) redeposition of degraded material in atmospheric plasmas . For other polymers further mechanisms have also been discussed: (iv) differential etching of crystalline and amorphous domains in cellulose fibres and PP, (v) sputtered Al particles from the plasma reactor wall that redeposit onto the surface of the polymer and act as masks during plasma etching of PMMA and PEEK, (vi) anisotropic ion bombardment of the polymer surface owing to local variation in curvature (experiments were performed on spin-coated PMMA, PS, PVDF, PEDOT, PPY and photoresist materials), (vii) spontaneous perturbation and topography formation of a thin film of polymer melt as a consequence of surface instabilities induced by the electric field, , or of buckling instabilities (viii) no reference to any mechanism. ,, …”
Section: Discussionmentioning
confidence: 99%
“…whereas the removal of material by ions is smaller at the peaks than in the valleys. The average etch rate for this plasma composition is between 1 and 2 nm · s −1 7…”
Section: Discussionmentioning
confidence: 99%
“…The oxidative decomposition of polymethylmetacrylate (PMMA) by microwave‐induced plasmas was reported by Gröning et al6 and confirmed for the dc‐plasma treatment process by Kaless et al7 It was demonstrated by X‐ray photoelectron spectroscopy (XPS) and Fourier‐transform infrared spectroscopy (FTIR) analysis that the PMMA's ester group degrades in a two‐step process resulting in a scission of the whole side chain. The formation of the surface structure may result as suggested by Koval8 from a self‐assembled etch mask on the surface that is generated due to the interaction of the plasma particles (ions and photons) with the material in surface‐near regions.…”
Section: Introductionmentioning
confidence: 90%